INCREASING EFFICIENCY OF MOBILITY OF THE NATURAL SCIENCE AND TECHNICAL UNIVERSITY UNDERGRADUATES - TRUBENOVA, Jaroslava; MISTINA, Juraj (Trends in education, 2011)
The lack of language and professional competence of students makes often a barrier for learning and studying at foreign universities within the European Union mobility programmes. The authors present a project which should help to solve the plight. The project aims at creating an electronic portal and building the modules as extracurricular source for the achievement of knowledge and professional communication skills.
Keywords: mobility; competence; efficiency; project; modulus.